Automatic interactive security monitoring system - Zeki, Akram M.; Eldaw, Elbaraa; Abubakar, Adamu; Haruna, Chiroma; Abdulkareem, Sameem (2013)
Over the years an increasing demand for an automated security system begins to emerge. Many applications that help in protecting life and properties are being developed. Most of them are aimed at improving the work of security personnel and security agencies. However, security is a responsibility of everyone not only the security agencies or security personnel alone. This paper present an interactive security monitoring system based on passive infrared motion detection sensor, which will capture the image of any intruding persons and share it to the entire people that are using the system on both Android platform and in an online portal display. The people on the system can communicate with each other and post information to a commonly accessible board in the online system to discuss any issues or to see if anyone recognizes the felons/intruder on the images. Images of interest can then be transmitted to law enforcement authorities. This could be use in anywhere that needs to be protected against intruder. It will be best use in kindergarten, primary school and or in a neighborhood. That is why we call it neighborhood watch security system (NWSS). Preliminaries evaluation indicated an accurate image captured in a real time with an avoidance of false alarm.